“Pagan Politics in the 21st Century: ‘Peace and Love’ or ‘Blood and Soil’?” - Strmiska, Michael F. (Pomegranate, 2018)
This essay begins by reviewing definitions and categories of modern Paganism (also variously termed contemporary or neo-Paganism) that the author first proposed in the 2005 book Modern Paganism in World Culture and then proceeds to discuss parallels with certain political trends in Europe and America today. Particular attention will be paid to how the rising tide of pro-nativist, anti-immigrant, and anti-Muslim sentiment in contemporary European and American politics mirrors certain views and values espoused by the more ethnically oriented forms of Paganism, even though this seeming convergence of interests between Pagans and rightists at the political level is undercut at the religious level by the right wing's firm adherence to Christianity and rejection of religious diversity. The essay proceeds to examine how competing nineteenth century visions of ethnic-centered nationalism and universal humanism are replicated today in the more ethnic and traditional types of Paganism versus those that are more eclectic and universalistic in their outlook. Pagan responses to the events of August 1-12, 2017 in Charlottesville, Virginia form the final topic.